1987
DOI: 10.1073/pnas.84.17.6277
|View full text |Cite
|
Sign up to set email alerts
|

Enterically transmitted non-A, non-B hepatitis: serial passage of disease in cynomolgus macaques and tamarins and recovery of disease-associated 27- to 34-nm viruslike particles.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(113 citation statements)
references
References 12 publications
(12 reference statements)
3
93
0
11
Order By: Relevance
“…This higher efficiency is needed when one needs to be certain that HEV, when present, causes infection. However, the natural route for HEV-transmission is most likely faecal-oral [6,31]. The natural route of transmission is required to study transmission dynamics and dynamics of HEV infection in individual animals.…”
Section: Introductionmentioning
confidence: 99%
“…This higher efficiency is needed when one needs to be certain that HEV, when present, causes infection. However, the natural route for HEV-transmission is most likely faecal-oral [6,31]. The natural route of transmission is required to study transmission dynamics and dynamics of HEV infection in individual animals.…”
Section: Introductionmentioning
confidence: 99%
“…Functional analysis of HEV proteins and nucleotide sequences involved in viral replication has been a difficult task, since an efficient cell culture system for HEV is not yet available. Therefore, most studies of HEV replication to date have been performed by transfection or infection of animals (3,8,23,24) or by overexpression of recombinant proteins in vitro (1,18,38,39,44). Agrawal et al reported that the 3Ј noncoding region (NCR) and an adjacent region of the positive strand of genotype 1 strains of HEV form putative stem-loop structures that affect the binding of recombinant viral RdRp in an in vitro assay (1).…”
mentioning
confidence: 99%
“…17 IEM studies on agglutination of VLPs in stools from HEVinfected individuals showed that diminishing IgG reactivity or seroconversion occurred when acute and serial convalescent phase sera from humans or monkeys were tested. 18 The results of these studies suggest that IgG anti-HEV could be a marker of acute infection. The persistence of IgG anti-HEV for one to four years has been demonstrated in some isolated cases.…”
Section: Long-term Antibody Statusmentioning
confidence: 76%